Baseline and stress-induced plasma corticosterone concentrations of mice selectively bred for high voluntary wheel running - Malisch, Jessica L.; Saltzman, Wendy; Gomes, Fernando R. [UNESP]; Rezende, Enrico L.; Jeske, Daniel R.; Garland Jr., Theodore (University of Chicago Press, 2007)
The hypothalamic-pituitary-adrenal (HPA) axis is important in regulating energy metabolism and in mediating responses to stressors, including increasing energy availability during physical exercise. In addition, glucocorticoids act directly on the central nervous system and influence behavior, including locomotor activity. To explore potential changes in the HPA axis as animals evolve higher voluntary activity levels, we characterized plasma corticosterone (CORT) concentrations and adrenal mass in four replicate lines of house mice that had been selectively bred for high voluntary wheel running (HR lines) for 34 generations and in four nonselected control (C) lines. We determined CORT concentrations under baseline conditions and immediately after exposure to a novel stressor (40 min of physical restraint) in mice that were housed without access to wheels. Resting daytime CORT concentrations were approximately twice as high in HR as in C mice for both sexes. Physical restraint increased CORT to similar concentrations in HR and C mice; consequently, the proportional response to restraint was smaller in HR than in C animals. Adrenal mass did not significantly differ between HR and C mice. Females had significantly higher baseline and postrestraint CORT concentrations and significantly larger adrenal glands than males in both HR and C lines. Replicate lines showed significant variation in body mass, length, baseline CORT concentrations, and postrestraint CORT concentrations in one or both sexes. Among lines, both body mass and length were significantly negatively correlated with baseline CORT concentrations, suggesting that CORT suppresses growth. Our results suggest that selection for increased locomotor activity has caused correlated changes in the HPA axis, resulting in higher baseline CORT concentrations and, possibly, reduced stress responsiveness and a lower growth rate. © 2007 by The University of Chicago. All rights reserved.
Keywords: corticosterone; baseline conditions; locomotion; metabolism; physiological response; rodent; adrenal gland; animal; blood; body size; body weight; cross breeding; exercise; female; genetics; histology; Institute for Cancer Research mouse; male; motor activity; mouse; physiology; sexual development; species difference; stress; Adrenal Glands; Animals; Body Size; Body Weight; Corticosterone; Crosses, Genetic; Female; Male; Mice; Mice, Inbred ICR; Motor Activity; Restraint, Physical; Sex Characteristics; Species Specificity; Stress; Animalia; Mus musculus